4CPS-001 Inappropriate use of proton-pump inhibitors – have we won the battle or are we still fighting?. (2nd March 2018) - Faschang, J; Hoppel, M; Laszloffy, B; Haider, D
Abstract : Background: Proton-pump inhibitors (PPIs) are effective drugs in the treatment of gastrointestinal disorders, such as gastroesophageal reflux disease, peptic ulcers, acid indigestion and heartburn. However, their associated gastroprotective effects led to a rapid increase in prescriptions and therefore non-appropriate use has risen dramatically in recent years. Besides putting patients at risk of suffering from potential side-effects, this prescription behaviour also represents a formidable financial burden for the healthcare system. To tackle this challenge, the regional health insurance fund issued a guideline to ensure adequate use of PPIs for in-house and discharged patients. Purpose: To analyse if PPI prescription patterns at an internal medicine ward are in accordance with published guidelines and if pharmaceutical interventions can reduce inappropriate PPI use. Material and methods: PPI use was evaluated over an observation period of 6 months starting in September 2016. Based on literature and health insurance guidelines, an evaluation sheet was compiled for each patient treated with PPIs during this time period. Personal data, risk factors, total number of medications, route of administration, onset and indication for PPI were documented. Prescriptions and compliance were discussed with physicians and patients, respectively. Results: In total, 143 patients were treated with PPIs during the observation period. We show that 57% of all PPI prescriptions were non-appropriate, meaning prescribed without indication according to the guidelines (81/143). Further key findings were that the most common unjustified prescription was the use of PPIs in the prevention of nonsteroidal anti-inflammatory drug-induced peptic ulcers in non-risk patients and that 90% of the PPI prescriptions were already pre-existing (129/143). The pharmaceutical intervention raised awareness about the issued guidelines and led to deprescription of 65% (53/81) of inappropriately prescribed PPIs. Conclusion: Despite the existence of guidelines, we found that the number of non-appropriate PPI prescriptions is still high. Most notably, the pharmaceutical intervention was highly successful and led to deprescription of a majority of non-appropriately used PPIs. These findings highlight the pharmacist's role as a vital link between inpatient and outpatient services, and show the potential of pharmaceutical intervention to innovate in the healthcare system. No conflict of interest